Lunar and Interplanetary Trajectories - Biesbroek, Robin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides readers with a clear description of the types of lunar and interplanetary trajectories, and how they influence satellite-system design. The description follows an engineering rather than a mathematical approach and includes many examples of lunar trajectories, based on real missions. It helps readers gain an understanding of the driving subsystems of interplanetary and lunar satellites. The tables and graphs showing features of trajectories make the book easy to understand. .
Introduction -- Launching to Interplanetary Orbits -- Transfer to a Planet -- Gravity Assist Manoeuvres -- Deep-Space Manoeuvres -- Lunar Transfers -- Arrival conditions at the planets -- Planetary Orbits -- Auxiliary Calculations.
Keywords: Aerospace engineering; Astronautics; Solar system; Aerospace Technology and Astronautics; Space Physics